Insatiable wealth preference: Evidence from Japanese household survey - Mika Akesaka; Ryo Mikami; Yoshiyasu Ono (Osaka University, Institute of Social and Economic Research (ISER), 2024)
This study theoretically considers household behavior with wealth preference and empirically investigates the validity of insatiable wealth preference using a nationally representative survey. With wealth preference, the marginal rate of substitution of asset holdings for consumption depends on the nominal interest rates of assets at each point in time. We focus on this property and find that the marginal utility of holding financial assets remains strictly positive as asset holdings increase and has a strictly positive lower bound, implying the insatiability of wealth preference. This property plays a crucial role in creating secular demand stagnation and expanding asset price bubbles.
Keywords: D12; E21; E43; E71; 330; wealth preference; survey data; secular stagnation; bubbles